Makna Simbolik Tokoh Gareng Bagi Masyarakat Milenial - Edwardus Bernard Elvis Berty; Denny Firmanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
The focus of this study is to explore the richness of symbolic meanings in Gareng figures for the Millennial community. Gareng is one of the figures from the Punakawan group. Punakawan is a group of puppet characters whose role is less visible when compared to the famous Five Pandavas. Because Gareng's role is not very visible, the philosophical meanings of Gareng are somewhat "vague", especially in the Millennial era, which emphasizes individualism and wants to win alone. The method used in this paper is to observe the symbols in the Gareng character, especially from the perspective of Ernst Cassirer's symbol theory. This review has very rich meaning for the Javanese themselves, especially for the Millennial community. Through the character Gareng who is full of wisdom, he is always able to bring happiness to others. He is also believed to be a royal advisor, because of his wisdom. In a state of limbs which can be said to be "imperfect", he is always able to be a carrier of perfection through his nature, words of wisdom, and so on. Here it can be seen that the Gareng figure has a value that is so noble for community, especially the Millennial community.